SOVIET MASCULINITY CRITICS IN FIŠKIN'S CHARACTER IN МОЙ ПАПА БАРЫШНИКОВ (MOJ PAPA BARYŠNIKOV) MOVIE - Prasetya, Aprilia; Kaprisma, Hendra (Sanata Dharma University, 2025)
This research discusses critiques of Soviet masculinity through Fiškin's character in Moj Papa Baryšnikov movie by Dmitrij Povolockij. This research aims to identify how Fiškin's character embodies a critique of Soviet masculinity. The author used representation theory from Stuart Hall (1997) and the content analysis method from Krippendorff (2019). In the analysis, the author displayed dialogue and screenshots of Chafetz's (1978) concept of masculinity, contextualized within Soviet reality. This research reveals that Fiškin's character does not represent the seven key characteristics of masculinity, including physical appearance, functional, sexual, emotional, intellectual, interpersonal, and personal. As a result, he serves as the antithesis of the ideal Soviet male. The filmmakers, benefiting from the post-Soviet era, form Fiškin’s character as a direct challenge to traditional Soviet masculinity, positioning this film as critical commentary on the era’s gender norms.